Антология выдающихся достижений в науке и технике. Часть 3: Открытие и изучение строения атома вещества - Баранов, М.И. (Електротехніка і електромеханіка, 2011)
A brief outline from the global history of study and discovery of atomic structure of matter, which is of fundamental significance for mankind in cognition of Nature, development of science and technology.